High sperm DNA fragmentation: do we have robust evidence to support antioxidants and testicular sperm extraction to improve fertility outcomes? a narrative review - Romano, Massimo; Cirillo, Federico; Spadaro, Daria; Busnelli, Andrea; Castellano, Stefano; Albani, Elena; Levi-Setti, Paolo Emanuele (Frontiers in Endocrinology, 2023)
To date, infertility affects 10% to 15% of couples worldwide. A male factor is estimated to account for up to 50% of cases. Oral supplementation with antioxidants could be helpful to improve sperm quality by reducing oxidative damage. At the same time, there is a growing interest in the literature on the use of testicular sperm in patients with high DNA fragmentation index (DFI). This narrative review aims to evaluate the effectiveness of supplementation of oral antioxidants in infertile men with high DFI compared to testicular sperm retrieval. The current evidence is non-conclusive because of serious risk of bias due to small sample sizes and statistical methods. Further large well-designed randomised placebo-controlled trials are still required to clarify the exact role of these to different therapeutic approaches.